The Influence of Brand Image and Service Quality on Purchasing Decisions - Triadi, Rahma; Suarha, Cecep; Kurniawati (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2024)
This study aims to explore the influence of brand image and service quality on purchasing decisions at Toko Gramedia Merdeka Bandung. Data were collected from 112 buyers at the store using the Accidental Sampling method. Data analysis employed multiple linear regression, correlation coefficient tests, t-tests, F-tests, and coefficient of determination tests. The results indicate that both brand image and service quality, both individually and collectively, have a significant positive impact on purchasing decisions. Brand image and service quality together explain a substantial portion of the variance in purchasing decisions, emphasizing the crucial role of these factors in attracting and retaining customers in a competitive market. These findings provide valuable insights for the management of Toko Gramedia Merdeka Bandung to enhance their marketing strategies and brand management to optimize customer experiences and expand their customer base in a dynamic market.